TOURIST OR EXPLORER? DELVING STUDENTS’ PREDILECTION AND ANXIETY IN SEMANTICS COURSE - Sagala, Rakhmat Wahyudin; Rezeki, Tri Indah (Universitas Muhammadiyah Makassar, 2024)
Within this particular study, the designations of